Investigation of the properties of a blockboard with strip filling faced with wood-fiberboard - Kushpit, Andriy; Kushpit, Oleksandra; Solonynka , Vasyl (Forestry, Forest, Paper and Woodworking Industry, 2017)
The design and possibility of using in the furniture production of a shield with a rail filling filled with HDF is analyzed. The expediency of the study of bending strength and bending deflection, determination of optimal base / coating restoration is substantiated